Heat exchange in the case of freon r22 condensation inside of horizontal-oriented tubes - Квасніков, В.П.; Горін, В.В. (Proceedings of National Aviation University, 2010)
In the article the questions of processes of heat exchange are examined during condensation of pair into a pipe. Theoretical and experimental researches, that the pair conducted for condensation into a horizontal smooth pipe at turbulent steam kernel and tape allowed first to get summarizing dependence for the local coefficients of heat emission in relation to the terms of work, characteristic for refrigeration units. Together with a koregovanoy formula for the criteria of determination of limit of existence along the pipe of the proper modes of flow of phases these dependences are basis for the construction of method of calculation of condensers of refrigeration units. Essence of method consists in experimental determination of the field of temperatures in the body of thick working area with the subsequent calculation of distributing of temperature on the surface of heat exchange, gradients of temperature, on verge of wall-energy source, and to distributing of coefficients of heat emission on the surface of heat exchange.